Pengaruh Brand Personality, Trust In The Brand, Attachment To The Brand Terhadap Commitment To The Brand - Didi Setiawan (Universitas Tarumanagara, 2020)
The aim of this study are : first, to explore the effect of brand personality towards commitment to the brand. Second, to explore the effect of trust in the brand towards commitment to the brand. Third, to explore the effect of attachment to the brand towards commitment to the brand. The method of data collection is convenience sampling. The samples of this research are colleted from 113 respondent. The technique of data analysis used in this study was multiple regression analysis via the SPSS computer programme version 26. The results are : first, brand personality hasn’t a positive impact towards commitment to the brand. Second, trust in the brand hasn’t a positive impact towards commitment to the brand. Third, attachment to the brand has a positive and the main impact towards commitment to the brand.